Bullying in Retailing: A Study of Non Branded Readymade Garment Sector - Amanjot Kaur (International Journal of Engineering and Management Research, 2020)
Bullying is a process in which people face criticism continuously in public and private, which humiliates that person. It has a detrimental impact on their performance, business, family, personal life and on their health also. The purpose of this paper is to address the problems faced by retailers of readymade garments who deal in non-branded clothes with the logo of original brand names. The research method used in this study is interview i.e. face to face and telephonic interview, in which 20 retailers selected through simple random sampling and shopkeepers express their views and opinions that what types of problems they are facing due to bullying and their consequences. Apart from this, retailers also give some suggestions to cope up with this situation.